STRUCTURAL BREAKS IN FOREIGN CAPITAL INFLOWS AND OUTPUT GROWTH: A ZIVOT-ANDREWS TEST (World Economics and Finance Bulletin, 2024)
Several financial and macroeconomic historical series display consistent trends until there is observed sudden permanent departure. With such occurrence traditional unit root test gives misleading inferences about the null ignoring the divergence in conventional stationarity test. This study detects single most significant structural break in foreign capital inflow series and domestic Nigerian outputs whose data originate with the World Bank. We further estimate class of two case models to establish two comparative regressions by first testing relationships vis-à-vis output growth using standard financial aggregates and later integrating single structural break into same series with dummy. This is implemented using endogenous Zivot-Andrew structural breakpoint estimator complemented with Chow breakpoint test before proceeding to perform Ordinary Least Square regression. Findings confirm breakpoint in historical series with 2005 as break date for major variants of foreign capital, while year 2010 represents break date in GDP. The dates rightly coincide with real structural policy implementation and political optimism. However, the null of unit root with break stands unrejected in GDP and external debt series but invalid in FDI and official development assistance. Further evidence reports positive influence of foreign capital inflows on GDP when break is ignored, however, including structural breaks modified the result such that official development assistance exerts negative influence on GDP.
Keywords: Official Development Assistance; External Debt; Economic Growth